Bone morphogenetic protein‐7 incorporated polycaprolactone scaffold has a great potential to improve survival and proliferation rate of the human embryonic kidney cells. Issue 6 (12th December 2018) - Saburi, Ehsan; Atabati, Hadi; Kabiri, Ladan; Behdari, Asma; Azizi, Mina; Ardeshirylajimi, Abdolreza; Enderami, Seyed Ehsan; Ghaderian, Sayyed Mohammad‐Hossein; Nafar, Mohsen; Parvin, Mahmoud; Omrani, Mir Davood
Abstract: Renal failures treatment has been faced with several problems during the last decades. Kidney tissue engineering has been created many hopes to improve treatment procedures with scaffold fabrication that can modulate kidney cells/stem cells migration to the lesion site and increase the survival of these cells at that site with imitating the role of the kidney extracellular matrix. In this study, bone morphogenetic protein‐7 (BMP7) as a vital factor for kidney development and regeneration was incorporated in the polycaprolactone (PCL) nanofibers and after morphological, mechanical, and biocompatible characterization, proliferation, and survival of the human embryonic kidney cells (HEK) were investigated using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT), flow cytometry, and gene expression while cultured on scaffolds. Mechanical properties of the PCL nanofibers modulated after combining with BMP7 and hydration degree, protein adsorption and cell adhesion were enhanced in PCL‐BMP7 compared to the pure PCL. Proliferation rate and growth increased significantly in HEK cells cultured on PCL‐BMP7 when compared with that of PCL and tissue culture plate, whereas these data were also confirmed via significant decrease in apoptotic genes expression level in HEK cell cultured on PCL‐BMP7. According to the results, PCL‐BMP7 demonstrated positive effects on the survival and proliferation rate of the kidney cells and showed has also a great potential to use as a bioimplant for kidney tissue engineering applications. Abstract : Bone morphogenetic protein‐7 (BMP7) was incorporated in the polycaprolactone (PCL) nanofibers; after morphological, mechanical, and biocompatible characterization, proliferation, and survival of the human embryonic kidney cells (HEK) were investigated using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT), flow cytometry, and gene expression while cultured on scaffolds. PCL‐BMP7 demonstrated positive effects on the survival and proliferation rate of the kidney cells and it has also a great potential to use as a bioimplant for kidney tissue engineering applications.